WHAT HAPPENS IF THE BROMELAIN IN Ananas comosus L. Merr. GIVEN TO PEOPLE LIVING WITH HIV/AIDS (PLWHA) ? : A REVIEW - Hariyanti, Reni; Sumarni, Sri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Human immunodeficiency virus /Acquired immunodeficiency syndrome (HIV/AIDS) is a global problem that requires serious treatment. Antiretroviral therapy (ART) has the potential to cause side effects and drug resistance for people living with HIV/AIDS (PLWHA). Alternative therapies using combination of bromelain and ART to maintain and improve immunity of PLWHA. The objective of the study was to describe the potential of bromelain in pineapple (Ananas comosus (L.) Merr) to increase the immune system of people living with HIV/AIDS. Methodology: The research method used a systematic literature review. The literature that this study used was search through in the Science Direct and Google Schoolar database. The article search used the keyword Ananas comosus (L.) Merr, HIV/AIDS healing pathway or bromelain enzyme healing pathway HIV/AIDS and Pineapple